EVALUATION OF PARENTAL GENOTYPES AND THEIR HYBRIDS AGAINST FUSARIUM WILT IN PIGEONPPEA - C. K. CHETHANA; S. MUNISWAMY; G. GIRISHA; YAMANURA; H. G. KENCHARADDI (The Bioscan, 2015)
An investigation was carried out at Agricultural Research Station, Gulbarga to develop and identify the superior hybrids coupled with enhanced resistance to fusarium wilt. A total of seventy eight hybrids and their parents were evaluated against fusarium wilt in wilt sick plot conditions. Out of 19 parental genotypes screened, seven genotypes showed resistant reaction, seven genotypes showed moderately resistant and remaining five genotypes recorded susceptible reaction to fusarium wilt. The parental genotypes TS-3R (6.0),LRG-41 (7.0), Asha (7.1) exhibited less wilt incidence, Out of seventy eight hybrids screened, twelve of them were found to be resistant and forty two hybrids showed moderate resistant reaction and twenty four hybrids showed susceptible reaction to wilt. The cross combinations ICPA-2048-4 x TS-3R (6.2), ICPA-2048-4 x Maruthi (7.1), ICPA-2092 x Asha (8.3) exhibited lower Percent Disease Index(PDI) values. It was interested to note from the present study that hybrids involving parents such as ICPA-2048-4, ICPA-2092, Asha, Maruthi, TS-3R, M-3 (GRG- 2009), LRG-41 and WRP- 1 showed resistant and moderately resistant reaction. Hence, these parental genotypes could be utilized in future breeding programme as donor source for development of fusarium wilt resistance cultivars of pigeonpea.